New YouthBuild grants expand second chances for at-risk youth in 31 states and the District of Columbia (Labor Department Documents and Publications, 2015)
Cincinnati Ohio $1,095,873 Previously-Funded YouthBuild Columbus Community School Columbus Ohio $1,100,000 New Applicant Franklin County Youth Build - Youth Over Us Columbus Ohio $1,100,000 Previously-Funded Community Action Commission of Fayette County Washington Court House Ohio $720,000 Previously-Funded Portland YouthBuilders Portland Ore. $1,100,000 Previously-Funded Auberle McKeesport Pa. $1,099,523 New Applicant Connection Training Services Philadelphia Pa. $1,100,000 Previously-Funded Philadelphia YouthBuild Charter School Philadelphia Pa. $1,100,000 Previously-Funded United Community Services for Working Families Reading Pa. $1,079,559 Previously-Funded The Providence Plan Providence R.I. $1,100,000 Previously-Funded Goodwill Industries of Upstate/Midlands South Carolina Greenville S.C. $1,080,000 New Applicant YouthBuild of Northeast Tennessee Elizabethton Tenn. $998,482 Previously-Funded Community Learning Centers, Inc. Fort Worth Texas $1,100,000 Previously-Funded SER-Jobs for Progress of the Texas Gulf Coast, Inc. Houston Texas $1,100,000 New Applicant Total Action For Progress Roanoke Va. $1,027,309 Previously-Funded Community Youth Services Olympia Wash. $1,100,000 Previously-Funded NorthEast Washington Educational Service District 101 Spokane Wash. $1,100,000 Previously-Funded Goodwill of the Olympics & Rainier Region Tacoma Wash. $1,100,000 Previously-Funded ADVOCAP, Inc. Fond du Lac Wis. $701,498 New Applicant Waukesha-Ozaukee-Washington Workforce Development Board Pewaukee Wis. $1,057,693 Previously-Funded Southern Appalachian Labor School Kincaid W.Va. $1,100,000 Previously-Funded Human Resource Development Foundation, Inc. Morgantown W.Va. $921,318 Previously-Funded ETA News Release: [09/16/2015] Contact Name: David Roberts or Joe Versen Phone Number: (202) 693-5945 or x4696 Release Number: 15-1836-NAT